Sosialisasi Budikdamber Guna Menjaga Kestabilan Ketahanan Pangan Keluarga - Lusianingrum, Farah Putri Wenang; Alfian, Iqbal; Maulana, Iqbal; Zahwa, ST; Wati, Helmalia; Abhinaya, Reswara Faza; Hanifah, Ayu Nur’aliyah; Gantara, Gerald Dewa; Akbar, Muhibudin; Firdausiah, Salsabila (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2023)
The increase in the unemployment rate in Bojong Pandan Village after the Covid-19 pandemic has threatened the stability of family food security. This condition threatens to make families in Bojong Pandan Village experience difficulties in meeting their basic needs through food. Budikdamber innovation is a solution to maintain family food security stability. However, the community still needs to gain knowledge and skills regarding Budikdamber, so there is a need for synergy between the village government and universities through community service activities. This service aims to increase the participant's knowledge and skills regarding Budikdamber. Implementation methods to support the achievement of the goals of this service include surveys, preparation, implementation, and evaluation. The results obtained from this community service activity were an increase in the participants' knowledge of 47.47%, and all participants could practice the tutorial activities for making Budikdamber. Follow-up of this activity will be routine monitoring at least once a month and innovating variations on fish and plant species other than catfish and water spinach.